Subnational Climate Policies: a proposal for monitoring in Rio Grande do Sul, Brazil (Sustainability in Debate, 2019)
Monitoring and evaluation of climate policies promote transparency and enable public engagement. Covering the period 2011 to 2017, this essay presents a qualitative analysis of the Policy on Adaptation to Climate Change adopted by the state of Rio Grande do Sul, as contribution to the debate about subnational adaptation policies. We use the set of tools developed by the Open Climate Network, which differs from the measurement of greenhouse gas emissions by the territory to assess the progress made in the implementation of the adaptation policies through public governance. While adoption by the state government started 2010, we conclude that this subnational adaptation policy still is in the stage of validation against the emission reduction targets proposed by the Paris Agreement, until 2025. Several adaptation policies are under way in Rio Grande do Sul, however, in a (still) fragmented mode. We identified gaps in the state budget, as well as governance constrains for the next step of implementation.